Programmable Base Editing in Mycobacterium tuberculosis Using an Engineered CRISPR RNA-Guided Cytidine Deaminase - Ding, Xin-Yuan; Li, Si-Shang; Geng, Yi-Man; Yan, Mei-Yi; Li, Guo-Bao; Zhang, Guo-Liang; Sun, Yi-Cheng (Frontiers in Genome Editing, 2021)
Multidrug-resistant Mycobacterium tuberculosis (Mtb) infection seriously endangers global human health, creating an urgent need for new treatment strategies. Efficient genome editing tools can facilitate identification of key genes and pathways involved in bacterial physiology, pathogenesis, and drug resistance mechanisms, and thus contribute to the development of novel treatments for drug-resistant tuberculosis. Here, we report a two-plasmid system, MtbCBE, used to inactivate genes and introduce point mutations in Mtb. In this system, the assistant plasmid pRecX-NucSE107A expresses RecX and NucSE107A to repress RecA-dependent and NucS-dependent DNA repair systems, and the base editor plasmid pCBE expresses a fusion protein combining cytidine deaminase APOBEC1, Cas9 nickase (nCas9), and uracil DNA glycosylase inhibitor (UGI). Together, the two plasmids enabled efficient G:C to A:T base pair conversion at desired sites in the Mtb genome. The successful development of a base editing system will facilitate elucidation of the molecular mechanisms underlying Mtb pathogenesis and drug resistance and provide critical inspiration for the development of base editing tools in other microbes.